Assessing Students' Numeracy Literacy Level using The Ethnoscience-SSI Integrated Test on Acid-Base Material - Pratiwi, Dian; Sudarmin, Sudarmin; Yamtinah, Sri (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2025)
Numeracy skills in the 21st century are essential because these skills not only support data analysis and number-based problem solving but are also needed in various aspects of life that affect the global community. The numeracy literacy of high school students has not been optimally trained, even though both abilities are needed to solve conceptual and contextual daily life problems in working on PISA and AKM items. This study was conducted to assess the numeracy literacy level of high school students in one of the cities in Central Java Province. As a survey with a quantitative approach, this study involved 150 high school students as respondents. The entire population became respondents in this study so the purposive sampling technique was applied. 24 out of 30 test items are empirically valid with a reliability value of 0.89. Data analysis was conducted using descriptive statistics to answer the numeracy literacy category of students. Based on the results, 35.60% was obtained which is included in the knowing level of numeracy literacy. The results of this study suggest more interactive and contextualized learning strategies to facilitate the transition to deeper understanding and application level.